PENGARUH DAYA TARIK IKLAN, KREATIVITAS IKLAN DAN KREDIBILITAS ENDORSER TERHADAP EFEKTIVITAS IKLAN DAN MINAT BELI PADA MINUMAN SERBUK BUAH MEREK NUTRISARI (Studi Pada Masyarakat Di Kota Malang) - Astiyanti, Gita Aprillia (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research aims to understand the influence of direct and indirect advertisingattraction, the creativity of advertising and the credibility of endorser to theeffectiveness of advertising and purchasing interest. A kind of this research isexplanatory research. This study takes the object community in Malang who neverwatch commercials Nutrisari Melt version at least 3 times. Participants in thisstudy as many as 85 people. The primary data collected through thequestionnaire. This research result indicates that attraction advertising andcredibility endorser directly influence on the effectiveness of advertising. Theeffectiveness of advertising also directly influence the purchasing interest. Theeffectiveness of advertising able to mediate attractiveness advertising andcredibility affecting endorser interest in purchasing. However, there is no director indirect influence of advertising creativity on the effectiveness of advertisingand purchasing interest. Therefore, it is important for marketers to create a modelof a story that is not easy to guess ads by viewers to influence the effectiveness ofadvertising and an indirect effect on purchasing interest.Keyword : attractiveness advertising, the creativity of advertising, credibilityendorser, the effectiveness of advertising, purchasing interest.